2013
DOI: 10.1899/13-077.1
|View full text |Cite
|
Sign up to set email alerts
|

Is the distribution pattern of the stone crayfish in the Carpathians related to karstic refugia from Pleistocene glaciations?

Abstract: BioOne Complete (complete.BioOne.org) is a full-text database of 200 subscribed and open-access titles in the biological, ecological, and environmental sciences published by nonprofit societies, associations, museums, institutions, and presses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 33 publications
0
17
0
Order By: Relevance
“…Pârvulescu et al . () assumed that stone crayfish outlasted the LGM in the Carpathian–Danube region and noble crayfish did not colonise this area until the retreat of glaciation. This hypothesis is supported by the heterogeneous distribution of haplotypes in Romania, indicating that the haplotypes did not evolve in the side channels of the Danube in Romania.…”
Section: Discussionmentioning
confidence: 99%
“…Pârvulescu et al . () assumed that stone crayfish outlasted the LGM in the Carpathian–Danube region and noble crayfish did not colonise this area until the retreat of glaciation. This hypothesis is supported by the heterogeneous distribution of haplotypes in Romania, indicating that the haplotypes did not evolve in the side channels of the Danube in Romania.…”
Section: Discussionmentioning
confidence: 99%
“…Although many populations of the species declined across its range, ongoing astacological research confirmed its wider presence in Bosnia and Herzegovina (Trožić-Borovac, 2011), Serbia, and Montenegro (Simić et al, 2008), as well as in Germany (Groß et al, 2008;Martin et al, 2008a). Substantial number of additional records has been also provided for previously underrepresented Romania (Pârvulescu and Zaharia, 2012;Pârvulescu et al, 2013), and the presumed original range of stone crayfish has been expanded to cover the Carpathian Arch there. All bulgarian Natura 2000 localities were recently investigated for presence of stone crayfish by Todorov et al (in press).…”
Section: > Austropotamobius Torrentium (Schrank 1803); Stone Crayfismentioning
confidence: 99%
“…; Pârvulescu et al . ; reviewed in Schmitt ). Therefore, this region offers an appropriate setting for studying biogeographical patterns of freshwater organisms at a more detailed scale, and to investigate both Quaternary and potential pre‐Pleistocene historical factors that might have influenced contemporary distribution patterns.…”
Section: Introductionmentioning
confidence: 99%